MULLIGAN MOBILIZATION IS MORE EFFECTIVE IN TREATING DIABETIC FROZEN SHOULDER THAN THE MAITLAND TECHNIQUE (International Journal of Physiotherapy, 2015)
Background: Patients with frozen shoulder suffer from significant pain and progressive limitation of shoulder active and passive movements. Such clinical problems are primarily treated conservatively. Physical therapy is an integral part in treatment of frozen shoulder. Rehabilitation may include various manual mobilization techniques in order to relieve pain and restore mobility and function. Therefore, this study aimed at comparing the effects of two different mobilization techniques (Mulligan Mobilization with Movement and Maitland end range mobilization) on improving shoulder pain, function and mobility in patients with diabetic frozen shoulder.Methods: Thirty patients were randomly and equally distributed into two groups: (1) Mulligan group receiving mobilization with movement, and (2) Maitland group receiving end range oscillatory mobilization. Treatment was given 3 times per week, for 6 consecutive weeks. Patients were evaluated before and after treatment with regards to shoulder pain severity and functional disability using the Shoulder Pain and Disability Index as well as for shoulder flexion, abduction, external and internal rotation range of motion using a digital level inclinometer.Results: Patients in the two groups showed significant improvement in all the measured variables over the treatment period (p